Transitions in Frequent to Daily Tobacco and Nicotine Use among Youth and Young Adults. (19th September 2022) - Do, Elizabeth K.; Tulsiani, Shreya; Vallone, Donna M.; Hair, Elizabeth C.
Abstract: Objective: To examine use and frequency patterns across e-cigarettes, cigarettes, and little cigars, cigarillos, and cigars (LCCs) over time. Methods: Data were obtained from the Truth Longitudinal Cohort (TLC), a nationally representative longitudinal cohort of youth and young adults. Latent class analysis was conducted to classify participants (n = 5274) into subgroups based upon frequency of use of cigarettes, e-cigarettes, and little cigars, cigarillos, and cigars (LCCs) in the past 30 days. Latent transition analysis was used to estimate the probability of use pattern transitions across 23 months (February 2018 to December 2019), adjusted for the effects of gender, race/ethnicity, financial situation, sensation seeking, parent education, and household smoking. Findings: Findings reveal four groups of tobacco product users: (1) frequent to daily cigarette users (9%), (2) frequent to daily cigarette and LCC users (3%), (3) frequent to daily e-cigarette users (10%), and (4) former or noncurrent tobacco users (78%). Although most respondents (69–94%) retained their initial user patterns during the observation period, results also indicate shifts between user groups. Notably, 14% of frequent to daily cigarette and LCC users transitioned to frequent to daily cigarette use, while 6% of frequent to daily cigarette and LCC users, 9% of frequent to daily cigarette users, and 4% of former or noncurrent tobacco users transitioned to frequent to daily e-cigarette use. Conclusion: Although most frequent to daily tobacco users stay with their primary product, there are transitions between frequent to daily cigarette, e-cigarette, and LCC use. Transition patterns may influence risk for nicotine addiction among youth and young adults. Thus, policies focused on preventing and reducing all tobacco use are needed to curb the risk of nicotine addiction among youth and young adults.